2022
DOI: 10.3390/plants11081071
|View full text |Cite
|
Sign up to set email alerts
|

Weed Management and Crop Establishment Methods in Rice (Oryza sativa L.) Influence the Soil Microbial and Enzymatic Activity in Sub-Tropical Environment

Abstract: Weed management has become the most important and inevitable aspect of crop management for achieving a higher rice yield. Nowadays, chemical herbicide application has become a popular practice for managing weeds in different rice cultures. However, herbicide application can have qualitative and quantitative impacts on soil microorganisms and soil enzymes, particularly in the case of new herbicide molecules and their indiscriminate use for a longer period. Further, different rice establishment methods also play… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…A natural herbicide is a kind of biocontrol for weed management in a cropping system [ 13 , 14 ]. Natural herbicides are considered to be safe for humans and the environment by modulating soil microorganisms, in addition to being readily biodegradable [ 15 ]. The herbicidal property is due to allelopathic activity of plants.…”
Section: Introductionmentioning
confidence: 99%
“…A natural herbicide is a kind of biocontrol for weed management in a cropping system [ 13 , 14 ]. Natural herbicides are considered to be safe for humans and the environment by modulating soil microorganisms, in addition to being readily biodegradable [ 15 ]. The herbicidal property is due to allelopathic activity of plants.…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, applying different herbicides in combination may reduce herbicide resistance (Mahajan & Chauhan, 2015). Chemical weed control has been shown to initially affect soil microbial populations, but this is followed by increased microbial population density and enzymatic activity as the crop progresses, particularly under UPTR (Pattanayak et al, 2022). Moreover, it has been observed that many reduced-tillage crop management practices promote small-seeded weeds (Chauhan, 2012), and we believe that this may also be true for UPTR.…”
Section: Introductionmentioning
confidence: 76%
“…Herbicides still represent the most popular tool for weed control, mainly in developing countries. However, the study conducted by Pattanayak et al [9] in an Indian sub-tropical environment highlighted that the chemical control with the herbicides bensulfuron, pretilachlor and bispyribac sodium negatively affected the soil microbial and enzymatic activity, whereas improved microbial populations and enzyme activities were noted in unpuddled transplanted rice (Oryza sativa L.) under organic weed management. Another negative effect related to the irrational application of herbicides is the spread of invasive or resistant weed species.…”
Section: New Advances In Chemical Weed Controlmentioning
confidence: 99%